2009
DOI: 10.1007/bf03245844
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Schiff base derived from sulfanilamide as an acid-base indicator

Abstract: The present paper firstly announces the possibility of using a Schiff base as an acid-base indicator. This surprising phenomenon can be considered as an interest due to the fact that Schiff bases are usually unstable in solutions and definitely undergo hydrolysis. It was found that such a specific observation depends merely upon the chemical structure and type of the substitute of amine that reacts with aldehyde to give the Schiff base. The latter reagent 4[(4-dimethylamino-benzylidene)-amino]-benzene sulfonam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…Many studies, describing the synthesis of similar Schiff base complexes and their applications for both ion sensing [2][3][4] and catalysis [5][6][7][8][9][10][11][12], have been reported. However, no studies are reported concerning the applications of transition metal Schiff base complexes as acid-base indicators, except a report on the application of a Schiff base as an acid-base indicator [13]. In this paper, we report spectroscopic and titrimetric evidence for possible applications of square planar Ni(II) and Cu(II) Schiff base complexes of N,N 0 -ethylenebis(acetylacetoniminate) ligand (L) as acid-base sensing materials and indicators.…”
Section: Introductionmentioning
confidence: 96%
“…Many studies, describing the synthesis of similar Schiff base complexes and their applications for both ion sensing [2][3][4] and catalysis [5][6][7][8][9][10][11][12], have been reported. However, no studies are reported concerning the applications of transition metal Schiff base complexes as acid-base indicators, except a report on the application of a Schiff base as an acid-base indicator [13]. In this paper, we report spectroscopic and titrimetric evidence for possible applications of square planar Ni(II) and Cu(II) Schiff base complexes of N,N 0 -ethylenebis(acetylacetoniminate) ligand (L) as acid-base sensing materials and indicators.…”
Section: Introductionmentioning
confidence: 96%
“…The derivatives of sulfonamide are very important because of their varied structures and biological activities [1]. These types of derivatives display interesting enzymatic inhibition towards the carbonic anhydrase (CA) isozymes CA I, II, IV, IX, and XII [2][3][4][5] and the cyclo-oxogenase (COX) enzymes COX-1 and COX-2 [6] still widely used for conditions such as antimicrobial drugs, antithyroid agents, antibacterial, antifungal, antitumor, antibiotics, acid-base indicator, potential anticancer agents [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The pK a value for the deprotonation of P1 resulted to be 11.03 ± 0.02, while the first protonation, on the N imine atom, is 6.36 ± 0.01 (pK b = 7.64) and the second protonation, on the N amine atom, is 4.27 ± 0.05 (pK b = 9.73), where the later pK a value is in agreement with other N,N′-dimethylaniline derivatives and Schiff bases. 58,59 On the other hand, the pK a values were also obtained by spectrophotometric technique to corroborate the assignment of the protonation events of individual functional groups (N imine and N amine ), 60 see Figure S3, Supporting Information. The pK a values were in good agreement with potentiometric titrations, being in fact that N imine is the first protonation with a pK a = 6.28 ± 0.02 (pK b = 7.72) and N amine is the second protonation, pK a = 4.31 ± 0.06 (pK b = 9.69).…”
Section: ■ Introductionmentioning
confidence: 99%